RELACIÓN DE LOS ESTADIOS DE LA OSTEOARTROSIS TEMPOROMANDIBULAR CON LOS CAMBIOS DIMENSIONALES DEL ESPACIO ARTICULAR TEMPOROMANDIBULAR, EVALUADO CON TOMOGRAFÍA COMPUTARIZADA CONE BEAM - Espinoza Calero, Karina (2017)
Introduction: The objective of this study is to determine the relationship between the stages of OA temporomandibular dimensional changes temporomandibular joint space. Methods: We analyzed tomograms of 120 joints of 60 patients aged 14 to 60 years treated in private clinics, in August 2009 / January 2012 Lima. With signs of degenerative osteoarthritis through (CBCT), left and right TMJ were evaluated independently for each patient. The assessment includes: condylar bone changes (erosion, flattening, osteophytes, sclerosis) and mandibular fossa (erosion, sclerosis), ranking at each stage of OA and then make measurements of anterior joint spaces, top and back of each joint in the sagittal plane. Were statistically analyzed by one-way ANOVA and post hoc Bonferroni test to see the significant difference of the joint space between each stage. Results: It was shown that there were significant differences at a significance level of p <0.05 from previous joint spaces (p <0.000), higher (p <0.000) and posterior (p <0.004). Being different in the initial and terminal stage in the anterior and superior joint spaces, the intermediate and terminal in the back space. Showing no difference in the initial and intermediate stage in the anterior and superior joint spaces, and intermediate and terminal stage in the back space. Conclusions: The present study showed that the joint spaces dimensions (anterior, superior and posterior), compared with normal parameters, diminish in each temporomandibular joint osteoarthrosis stage.